An Evaluation of Coding Violation Focusing on Change History and Authorship of Source File - Aji Ery Burhandenny; Hirohisa Aman; Minoru Kawahara (International Journal of Networked and Distributed Computing (IJNDC), 2017)
This paper focuses on an evaluation of coding violation warned by a static code analysis tool while considering the change history of violation and the authorship of source file. Through an empirical study with data collected from seven open source software projects, the following findings are reported: (1) the variety and the evaluation of a coding violation tend to vary accroding to the authoring type of the source file; (2) while important violations tend to vary from project to project, about 30% of violations are commonly disregarded by many programmers.